How to extract reliable core-volume fractions from core-shell polycrystalline microstructures using cross sectional TEM micrographs. Issue 8 (July 2017) - Morshead, F.H.; Foeller, P.Y.; Freeman, C.L.; Zhang, H.; Reaney, I.M.; Sinclair, D.C.; Dean, J.S.
Abstract: A reliable method of extracting core-volume fraction from TEM micrographs of core-shell polycrystalline microstructures is presented. Three commonly used averaging methods based on a simple spherical model are shown to consistently underestimate the core-volume fraction due to the interpretation of a 3D structure from a 2D slice. The same trend is also revealed using Voronoi tessellated structures to mimic polycrystalline ceramics. In some cases the underestimate is less than half the true core-volume fraction. We show that using a new maximum core-volume fraction methodology can improve the extracted value to a consistent error of less than 5%. This approach uses a value taken from the largest core-volume fraction measured from 10 grains that exhibit a core-shell microstructure. This provides increasing accuracy and improvements in the confidence of the measurement when extracting core-volume fractions of polycrystalline ceramics from 2D TEM micrographs.